If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -2v + 7v = 2v + 16 + -7 Combine like terms: -2v + 7v = 5v 8 + 5v = 2v + 16 + -7 Reorder the terms: 8 + 5v = 16 + -7 + 2v Combine like terms: 16 + -7 = 9 8 + 5v = 9 + 2v Solving 8 + 5v = 9 + 2v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-2v' to each side of the equation. 8 + 5v + -2v = 9 + 2v + -2v Combine like terms: 5v + -2v = 3v 8 + 3v = 9 + 2v + -2v Combine like terms: 2v + -2v = 0 8 + 3v = 9 + 0 8 + 3v = 9 Add '-8' to each side of the equation. 8 + -8 + 3v = 9 + -8 Combine like terms: 8 + -8 = 0 0 + 3v = 9 + -8 3v = 9 + -8 Combine like terms: 9 + -8 = 1 3v = 1 Divide each side by '3'. v = 0.3333333333 Simplifying v = 0.3333333333
| 3(7x-5)+3(15-4x)=2(4x+1)-1 | | 14t-22+5t=12t-8 | | 5x-(3x-3)=17 | | 60n-9n=60 | | 9k=12 | | -(8-9a)-(8+8a)-25=-(2-7a)+(-a)+1 | | -8-b=2 | | -16=5(2x-11) | | y=.5mx | | 9s-8+4s=7s+16 | | 12-(x+8)=6x-3 | | (X^2-x-20)(5x-20)=0 | | 4r-3+3r=-2r+5-17 | | 8x-1=x+20 | | -5(-8+n)=25 | | -10(a-7)=110 | | 20q-11-3q=9q+43 | | 6[z-(8z+51)+9]=4(2+6) | | (2x-10x)+(3x-10)=9 | | -57x^2y^2z-88x^2y^2z= | | 5n+3+6n=10n+9-n | | 45+45+6h=303 | | 5(t^2-1)=4t^2+8t+7 | | 5n+3n+6n=10n+9-n | | -4-9.6+5c=0 | | 0.4=0.9+3t | | 2p-2(2-4p)=5(p-6)-19 | | 4m+6-7m+9=18 | | 24a^2+16b^2-17a^2= | | 7l+14-5l=-8 | | 7y-2+4+3y=-20 | | -8(2x-1)=35 |